Effects of competition and seasonality on life history traits of bank voles - Eccard, Jana Anja (2002)
Populations of small mammals can fluctuate in size responding to social and environmental variation, such as density-dependence, density of competitors, predation, seasonality, and/or food availability. Little is known about how the variation of population size can be mediated through individual behaviour, and how changes in individual life history, in turn, can respond to population size. In this thesis, life history variables of bank vole females (Clethrionomys glareolus, an arvicoline rodent) were investigated in experiments manipulating density of competitors and con-specifics in large outdoor enclosures. Voles were bred in the laboratory and released in experimental populations of known age structure and reproductive history in order to study life history traits at different ages. In four experiments, half of the enclosures were manipulated by adding voles of a competitor species, the field vole Microtus agrestis and the other half served as controls. In one experiment enclosures were manipulated by food addition. In all experiments, density of con-specifics was closely monitored, and seasonal change in the environment was used as a co-variate when interpreting the results. Presence of field vole competitors decreased predominantly the survival of bank vole females, whereas the breeding rate or the maturation of young females was not altered. Different cohorts of females were differently affected, with year born breeding females more susceptible to the effects of field vole competition than over-wintered breeding females. No survival decrease was found in young, immature females and in adults over the non-breeding season. Based on these results, it may be an advantageous strategy for year born females, when field vole competitors are abundant, to delay maturation, because once matured, her future survival chances could be decreased. High density of con-specifics decreased the reproduction of individuals by delaying maturation in spring or by decreasing the rate of breeders in summer. Survival was not affected by con-specifics. The results suggest that population interaction with a different vole species influences not the same life history traits than density-dependence of con-specifics does, and thus may alter the dynamics of population size fluctuations in different ways.